PEMBELAJARAN PAJAK UMKM BAGI SISWA SISWI - Syanti Dewi; Jesslyn Yohanata; Devina (Jurnal Serina Abdimas, 2026)
The development of Micro, Small, and Medium Enterprises (MSMEs) plays a crucial role in supporting Indonesia's economic growth and increasing state revenue through tax contributions. However, tax awareness among the younger generation remains low. Empowering MSMEs with tax compliance requires basic training from school. Therefore, this Community Service (PKM) activity was conducted at Sinar Dharma High School with the aim of improving students' understanding of tax obligations and their relationship to MSME development. This activity introduced the basic concepts of MSME taxation, including calculating MSME income tax and its benefits for national development. This activity was conducted at a high school in West Jakarta with students in grades 10 (ten) to 12 (twelve). The implementation method included interactive presentations, discussions, question and answer sessions, and quizzes. Students demonstrated high enthusiasm by actively participating in the Q&A session. The results of the activity showed an increase in students' understanding and awareness of MSME taxes. It is hoped that through early tax education, students can become a tax-conscious generation and be able to support the growth of small and medium enterprises. Overall, the Community Service Program (PKM) on tax education for high school students was well-executed and smoothly executed. The series of activities ran according to plan and received a positive response from participants. This resulted in increased understanding and awareness of the importance of tax compliance in supporting the development of MSMEs in Indonesia. Perkembangan Usaha Mikro, Kecil, dan Menengah (UMKM) memiliki peranan penting dalam mendukung pertumbuhan ekonomi Indonesia dan peningkatan pendapatan negara melalui kontribusi pajak. Namun, tingkat kesadaran pajak di kalangan generasi muda masih tergolong rendah. Dalam pemberdayaan pajak untick UMKM, diperlukan pelatihan dasar dari mulai bangku sekolah. Oleh karena itu, kegiatan Pengabdian kepada Masyarakat (PKM) ini dilaksanakan di SMA Sinar Dharma dengan tujuan untuk meningkatkan pemahaman siswa-siswi terhadap kewajiban perpajakan dan kaitannya dengan perkembangan UMKM. Kegiatan ini memperkenalkan konsep dasar perpajakan UMKM, termasuk perhitungan pajak penghasilan UMKM serta manfaatnya bagi pembangunan nasional. Kegiatan ini dilaksanakan di sekolah menengah atas di Jakarta Barat dengan siswa kelas 10 (sepuluh) sampai dengan kelas 12 (dua belas). Metode pelaksanaan meliputi presentasi interaktif, diskusi, jawab pertanyaan dan kuis. Siswa-siswi menunjukkan antusiasme tinggi dengan berpartisipasi aktif dalam tanya jawab. Hasil kegiatan menunjukkan peningkatan pemahaman dan kesadaran siswa-siswi terhadap pajak UMKM. Diharapkan melalui edukasi pajak sejak dini, siswa dapat menjadi generasi yang sadar pajak dan mampu mendukung pertumbuhan usaha kecil dan menengah. Secara keseluruhan, kegiatan PKM mengenai edukasi perpajakan bagi siswa-siswi SMA terlaksana dengan baik dan lancar, dan kegaitan dari rangkaian tersebut sesuai dengan rencana, serta mendapatkan respons positif dari peserta. Sehingga berhasil meningkatkan pemahaman dan kesadaran terhadap pentingnya kepatuhan pajak dalam mendukung perkembangan UMKM di Indonesia.